Notes to Philosophy 167: Class 8 -- Descartes' Principia: Laws of Motion -- Complete. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Kepler and Galileo: The Second Post-Copernican Generation -- Descartes: The Third Post-Copernican Generation -- Descartes' "Mechanical Philosophy" -- Descartes' Laws of Motion -- Descartes' Rules of Perfectly Elastic Impact.; Section: Class 8, Complete.